Bandwidth enhancement of dual-band bi-directional microstrip antenna using complementary split ring resonator with defected structure for 3/5 GHz applications - Charernkiat Pochaiya; Srawouth Chandhaket; Prapan Leekul; Jhirat Mearnchu; Tanawut Tantisopharak; Thunyawat Limpiti (International Journal of Electrical and Computer Engineering (IJECE), 2022)
This paper presents a bandwidth enhancement of a dual-band bi-directional rectangular microstrip patch antenna. The novelty of this work lies in the modification of conventional rectangular microstip patch antenna by using the combination of two techniques: a complementary split ring resonator (CSRR) and a defected patch structure (DPS). The structure of antenna was studied and investigated via computer simulation technology (CST). The dimension and position of CSRR on the ground plane was optimized to achieve dual bandwidth and bi-directional radiation pattern characteristics. In addition, the bandwidths were enhanced by defecting suitable shape incorporated in the microstrip patch. A prototype with overall dimension of 70.45×63.73 mm2 has been fabricated on FR-4 substrate. To verify the proposed design, the impedance bandwidth, gain, and radiation patterns were carried out in measurements. The measured impedance bandwidths were respectively 560 MHz (3.08-3.64 GHz) and 950 GHz (4.64-5.59 GHz) while the measured gains of each bandwidth were respectively 4.28 dBi and 4.63 dBi. The measured radiation patterns were in good agreement with simulated ones. The proposed antenna achieves wide dual bandwidth and bi-directional radiation patterns performances. Consequently, it is a promising candidate for Wi-Fi or 5G communications in specific areas such as tunnel, corridor, or transit and rail.